Perioperative Management of a Giant Ovarian Tumour in an Adolescence with Severe Scoliosis and Unilateral Diaphragmatic Dysfunction: A Case Report - Gezy Wita Giwangkancana; Andi Kurniadi; Yunita Susanto Putri; Euis Maryani (Faculty of Medicine, Universitas Padjadjaran, 2021)
Though giant ovarian tumor are rare but due to the limitations in oncology surgery during the COVID-19 pandemic, many oncology patients are presented with a more severe stage and giant ovarian tumors may be more commonly seen during this period. The aim of this case report study was to describe the perioperative management of an adolescent patient with a giant ovarian tumor, severe scoliosis, and unilateral diaphragm dysfunction. An 18-years-old girl weighing 28 kgBW came with a giant abdominal mass that extended to her thoracic and back areas. The patient had a history of severe scoliosis since childhood. She had signs of respiratory distress and was not comfortable lying down. Preoperatively, the surgeon used ultrasonography to guide cyst puncture using a thoracic tube and 6,500 cc of mucinous fluid was drained. Inhalational induction with preservation of spontaneous breathing was performed. Two massive masses filled the entire abdominal area, adhering to the peritoneum while pushing and tenting the diaphragm cranially and laterally to the right and bilateral salpingo-oophorectomy was conducted. Serial radiological examinations showed unilateral diaphragmatic dysfunction and a progressing ventilator associated pneumonia. Improving post-operative outcome of patients with giant intraabdominal masses must include preoperative assessment of potential peri-operative respiratory complications, preparation of intraoperative hemodynamic, and ventilatory disturbances with gentle weaning and multidisciplinary approach during the post-operative care to assess readiness of ventilator weaning. Manajemen Perioperatif Pasien dengan Tumor Ovarium Permagna pada Remaja dengan Skoliosis Berat dan Gangguan Diafragma UnilateralTumor ovarium berukuran masif pada anak jarang ditemukan di masa moderen karena perbaikan sistem pelayanan kesehatan namun di masa COVID-19, kasus dapat ditemukan karena hambatan pelayanan pembedahan onkologi. Laporan kasus ini bertujuan melaporkan manajemen perioperatif pada pasien remaja dengan tumor ovarium massif, skoliosis berat dan disfungsi diafragma. Remaja berusia 18 tahun dengan berat 35 kilogran datang dengan massa abdomen sangat besar disertai riwayat skoliosis. Pasien memiliki tanda ancaman gagal napas dan tidak nyaman pada posisi berbaring dan hanya dapat beristirahat dalam posisi duduk. Sebelum induksi, dokter bedah melakukan punksi massa dan didapatkan 6.500 cc cairan musin. Pasien diinduksi dengan napas spontan menggunakan gas anestesi. Bilateral salfingoofarektomi dilakukan dan pascaoperasi pasien dirawat di ruang intensif. Selama masa pemulihan pasien sulit disapih dari ventilator dan hasil pemeriksaan radiologis berulang menunjukkan tanda disfungsi diafragma dan pneumonia. Simpulan, meningkatkan hasil keluaran pada pasien dengan massa intraabdomen massif harus meliputi pemeriksaan preoperatif yang cermat mengenai komplikasi pernafasan perioperative, persiapan permasalahan hemodinamik intraoperative dan strategi penyapihan dari ventilator yang efektif dengan melibatkan pendekatan multidisiplin.